Neurological deterioration as a result of improper neck position detected by intraoperative neurophysiological monitoring in a cervical stenosis patient: A case report. Issue 11 (19th March 2021) - Yu, Tong; Wu, Jiu-Ping; He, Tao; Ruan, Yao-Kuan; Liu, Qin-Yi
Abstract: Rationale: Intraoperative neurophysiological monitoring (IONM) is widely used in spinal surgeries to prevent iatrogenic spinal cord injury (SCI). Most surgeons focus on avoiding neurological compromise intraoperatively, while ignoring the possibility of nerve damage preoperatively, such as neck positioning. Thus, this study aims to report a case with transient neurological deterioration due to improper neck position detected by IONM during cervical surgery. Patient concerns: A 63-year-old male patient had been suffering from hypoesthesia of the upper and lower extremities for three years. Diagnoses: Severe cervical stenosis (C5-C7) and cervical ossification of a posterior longitudinal ligament. Interventions: The cervical stenosis patient underwent an anterior cervical corpectomy decompression and fusion (ACDF) surgery with the assistance of IONM. When the lesion segment was exposed, the SSEP and MEP suddenly elicited difficulty indicating that the patient may have developed SCI. All the technical causes of IONM events were eliminated, and the surgeon suspended operation immediately and suspected that the IONM alerts were caused by cervical SCI due to the improper position of the neck. Subsequently, the surgeon repositioned the neck of the patient by using a thinner shoulders pad. Outcomes: At the end of the operation, the MEP and SSEP signals gradually returned to 75% and 80% of the baseline, respectively. Postoperatively, the muscle strength of bilateral biceps decreased from grade IV to grade III. Besides, the sensory disturbance of both upper extremities aggravated. However, the muscle power and hypoesthesia were significantly improved after three months of neurotrophic therapy and rehabilitation training, and no complications of nerve injury were found at the last follow-up visit. Lessons: IONM, consisting of SSEP and MEP, should be applied throughout ACDF surgery from the neck positioning to suture incisions. Besides, in the ward 1to 2 days before operation, it is necessary for conscious patients with severe cervical stenosis to simulate the intraoperative neck position. If the conscious patients present signs of nerve damage, they can adjust the neck position immediately until the neurological symptoms relieve. Therefore, intraoperatively, the unconscious patient can be placed in a neck position that was confirmed preoperatively to prevent SCI.